Impact of green bonds on CO2 emissions and disaggregated level renewable electricity in China and the United States of America - Mustafa Tevfik Kartal; Ugur Korkut Pata; Andrew Adewale Alola (Humanities & Social Sciences Communications)
Abstract Green financial products have emerged that can benefit economic actors in financing green initiatives to promote renewable energy and enable carbon neutrality. Against this backdrop, the study examines the impact of green bonds (GBs) on carbon dioxide (CO2) emissions and renewable electricity generation (EG) in China and the USA, the leading countries in terms of GB issuance and CO2 emissions. To this end, the study conducts a disaggregated-level analysis by applying novel nonlinear quantile methods between January 2, 2019, and July 31, 2023. The results demonstrate that at higher quantiles; (i) GBs mainly have a dampening impact on CO2 emissions from the transportation sector in China and the USA; (ii) GBs have a stimulating impact on solar and wind EG in China; (iii) GBs have a diminishing impact on all types of EGs in the USA. Thus, GBs have an impact on carbon neutrality and renewable energy, which differs by quantiles, sectors, and EG sources. Accordingly, various policy implications are discussed in terms of further contributions of GBs to carbon neutrality and renewable energy in China and the USA.